2021
DOI: 10.1111/pedi.13298
|View full text |Cite
|
Sign up to set email alerts
|

Time trend in excess mortality in children with type 1 diabetes from 1987 to 2016 in mainland France

Abstract: Background: Mortality risk for children with type 1 diabetes (T1D) is unknown in France and their causes of death are not well documented.Aim: To determine the standardized mortality ratios (SMRs) and causes of death in children aged 1-14 years with T1D from 1987 to 2016. Methods:The French Center for Epidemiology on Medical Causes of Death collected all death certificates in mainland France. SMRs, corrected SMRs (accounting for missing cases of deaths unrelated to diabetes), and 95% confidence intervals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Despite the developments in clinical care in recent years, the mortality risk for people developing type 1 diabetes in childhood remains high in young adult life before the onset of chronic complications. 24,25…”
Section: Rate Controlmentioning
confidence: 99%
“…Despite the developments in clinical care in recent years, the mortality risk for people developing type 1 diabetes in childhood remains high in young adult life before the onset of chronic complications. 24,25…”
Section: Rate Controlmentioning
confidence: 99%
“…Recent data are important as treatment and management of type 1 diabetes is rapidly evolving. Mortality rates for people with type 1 diabetes have decreased over the last two decades by ∼2.1% per year in Australia and up to 5.8% per year in Denmark [2]; however, as Donzeau et al [3] identified, few studies of childhood-onset type 1 diabetes have included recent mortality data from 2010 onwards.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, hypoglycemia remains the most common acute complication of T1D. It can give rise to a wide range of symptoms, from mild events with palpitations, sweatiness and shakiness to severe with neurological symptoms, seizures with coma and potentially death 14 15. Even mild hypoglycemic events, and also fear of hypoglycemia, are a hurdle for achieving optimal glycemic levels.…”
Section: Introductionmentioning
confidence: 99%